Validation of an instrument to assess nurses’ level of knowledge on the prevention and treatment of individuals with venous ulcers - Oliveira de Sousa, Alana Tamar; Soares Formiga, Nilton; dos Santos Oliveira, Simone Helena; de Vasconcelos Torres, Gilson; Lopes Costa, Marta Miriam; Guimarães Oliveira Soares, Maria Júlia (Investigación y Educación en Enfermería, 2016)
Objective. Validating an instrument to assess nurse knowledge related to preventing and treating individuals with venous ulcer (VU) Methods. This is an exploratory study, conducted with 78 primary health care nurses. These professionals answered the questionnaire with twelve items pertaining to knowing and doing while addressing the person with VU. SPSS for Windows, version 21.0, with descriptive analyses and Pearson correlation was used for data analysis. Results. The measurement of questionnaire reliability, from Cronbach’s alpha, revealed in the Theoretical Knowledge Domain (TKD), 0.88 alpha, and in the Practical Knowledge Domain (PKD), 0.70 alpha, indicators that guaranteed reliability of such a measurement for the extracted sample. With regard to the correlation between TKD and PKD and Nursing Care to the Person with VU, those were significant and strong in almost all items. The bi-factorial model, with theoretical and practical domains, is what best explains the nurse assistance for the person with VU. The nurse that knows one or both domains in treating wounds, probably, will allow for greater dominance over VU and in assisting the person with VU. Conclusion. The validated version showed reliability, enabling thus the other professionals to tailor the same methodology to other topics, identifying the ramifications of knowing and doing and, thereby,strengthening gaps in the Nursing Education area. How to cite this article: Sousa ATO, Formiga NS, Oliveira SHS, Torres GVT, Costa MML, Soares MJGO. Validating an instrument to assess nurse knowledge related to preventing and treating individuals with venous ulcer. Invest. Educ. Enferm. 2016; 34(3): 433-443